Application of Personalised System of Instruction Model in Learning during the Covid 19 Pandemic to Physical Education Learning Outcomes - Muhamad Ismam Muhdian; Rian Kurnia; Herman Subarjah; R. Boyke Mulyana; Hasanul Fitrah Alba (Universitas PGRI Palembang, 2022)
The COVID 19 pandemic that affects almost all countries in the world is a disaster for the entire population of the earth. This disaster caused disruption of all lines including education. As a result of this pandemic came the term distance learning. The study is a combination of distance learning and limited face-to-face learning. The purpose of this study is to find out the application of personalised system of instruction learning model in the learning process during the covid 19 pandemic to the learning outcomes of upper elementary students. The sample used was 5th grade elementary students who numbered 28 people divided into 2 groups. The research method used is the true experimental method with the design of The Randomized Pretest-Posttest Control Group Design. The results of this study obtained the influence of the application of personalised system of instruction learning model in the learning process during the covid 19 pandemic on motivation and learning outcomes in upper elementary students.